PRODUCTIVITY AND EFFICIENCY OF INTERNATIONAL AIRLINES - Araujo Junior, Antonio Henriques de (Revista Ciências Exatas, 2023)
This paper presents the published results of post-doctoral research conducted at the Brazilian Aeronautics Technological Institute (ITA), Brazil. The objective of this study is to evaluate the operational performance of the major Brazilian carriers during the period immediately following the deregulation of air transport in Brazil, comparing their performance with representative international counterparts. The process of deregulation of air transport in Brazil began in 2001 with the implementation of Law No. 10,365, known as the "Open Skies Law." This law allowed the entry of foreign airlines into the Brazilian domestic market and facilitated the operation of low-cost airlines. In this research, the aim was to compare the evolution of productivity and operational performance of full-service companies (FSC), regional airlines (RA), and low-fare/low-cost companies (LCC). The research concluded that Brazilian companies operating domestically demonstrated a productivity growth rate of 7.7% per year, surpassing the average of the sample. Additionally, the analysis revealed that low-cost companies exhibited superior operational performance compared to the full-service and regional airlines.